Towards an Integrative Currency Area - Dobija, Mieczysław (Central and Eastern European Economic Review, 2016)
Optimal currency area theory is the supporting knowledge base of the European euro area. However, the euro area does not work seamlessly, and many doubts have arisen in regard to the theoretical foundations of the project and the procedures used to implement it. In particular, the accession of new members remains doubtful. This paper develops a diagnosis and proposes modifications to the theoretical foundations of the optimal currency area in line with recent developments in economic thinking. This progress is focused on the application of a triad of abstract notions – capital, labour, and money – and the use of essential notions, among which labour self-financing is the most significant. The analysis leads to an integrative as opposed to a discriminative currency area. Another aim of this paper is to show how to reshape the existing discriminative euro area as an area involving states that do not fulfill the Maastricht criteria. An integrative area can involve states with different productivity levels, allowing the fixed exchange rate criterion to be withdrawn. In addition, the application of self-financing removes the problem of dominant public debt. A major part of this paper develops a measure of labour productivity and applies it to procedures involving the use of exchange rates.